Attitudes are associated with the drug use profiles of middle school adolescents: A latent class analysis. (January 2021) - Garcia-Cerde, Rodrigo; Valente, Juliana Y.; Sanchez, Zila M.
Highlights: Girls and older students have a greater chance to be alcohol users-binge drinkers and polydrug users. Behavioral intention predictors should be core elements for implementing and evaluating school-based drug use prevention programs. Drug use prevention programs should focus on deconstructing positive attitudes, mainly. Abstract: The association between positive and negative attitudes and drug use profiles is examined. Participants were public middle school students ( N = 5213; 49.9% girls; M age= 13.2 years) in three Brazilian cities. Analysis was performed using baseline surveys of a randomized controlled trial of the # Tamojunto2.0 drug use prevention program. We validated the attitudes construct via a confirmatory factor analysis and performed a simultaneous multinomial regression with a latent class analysis. Three latent classes were identified: abstainers/low users (ABS) (63.4%), alcohol users/binge drinkers (ALC) (29.5%), and polydrug users (POL) (7.1%). An association gradient was found between attitudes and latent classes. Using ABS as reference, a direct association was identified between positive attitudes and ALC and POL. An inverse association was found between negative attitudes and POL only. Girls and older students were more likely to be ALC and POL. These findings, from a large probabilistic sample, provide guidance that drug use prevention programs should focus on deconstructing positive attitudes -mainly- and broadening negative attitudes, and should adapt their thematic content by considering the differential drug use possibilities among girls and older students.